Healthcare Interpreting and Informed Consent: What is the Interpreter’s Role in Treatment Decision-Making? - Clifford, Andrew (TTR, 2005)
This article examines the part that healthcare interpreters play in cross-cultural medical ethics, and it argues that there are instances when the interpreter needs to assume an interventionist role. However, the interpreter cannot take on this role without developing expertise in the tendencies that distinguish general communication from culture to culture, in the ethical principles that govern medical communication in different communities, and in the development of professional relationships in healthcare. The article describes each of these three variables with reference to a case scenario, and it outlines a number of interventionist strategies that could be potentially open to the interpreter. It concludes with a note about the importance of the three variables for community interpreter training.Keywords: community interpreting, informed consent, role of the interpreter, healthcare.